2013
DOI: 10.1109/tuffc.2013.2546
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian speckle tracking. Part II: biased ultrasound displacement estimation

Abstract: Ultrasonic displacement estimates have numerous clinical uses including blood-flow, elastography, therapeutic guidance and ARFI imaging. These clinical tasks could be improved with better ultrasonic displacement estimates. Traditional ultrasonic displacement estimates are limited by the Cramer-Rao lower bound (CRLB). The CRLB can be surpassed using biased estimates. In this paper a framework for biased estimation using Bayes’ theorem is described. The Bayesian displacement estimation method is tested against s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…These methods—termed Bayesian speckle tracking or Bayesian regularization—use prior knowledge of the estimation task in order to improve the current estimate. Byram et al showed that Bayesian speckle tracking could produce displacement estimates with a lower mean-square error relative to a CRLB-limited estimator for bulk displacement, strain-based elastography, and radiation-force based elasticity imaging [13]. Mc-Cormick et al proposed an iterative, Bayesian regularization method and showed that significant improvements in estimate quality could be achieved in very few iterations for ultrasound strain images with strains greater than 5% [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods—termed Bayesian speckle tracking or Bayesian regularization—use prior knowledge of the estimation task in order to improve the current estimate. Byram et al showed that Bayesian speckle tracking could produce displacement estimates with a lower mean-square error relative to a CRLB-limited estimator for bulk displacement, strain-based elastography, and radiation-force based elasticity imaging [13]. Mc-Cormick et al proposed an iterative, Bayesian regularization method and showed that significant improvements in estimate quality could be achieved in very few iterations for ultrasound strain images with strains greater than 5% [14].…”
Section: Introductionmentioning
confidence: 99%
“…While both approaches demonstrate the reduction in estimate error that can be realized with these techniques, there is room for improvement. For example, Byram et al proposed a directionally-dependent prior scheme, and hypothesized that the falsely-imposed causality limited its performance [13]. McCormick et al reported a reduction in image quality for strain-fields smaller than 1% [14], making it unclear how suitable their approach will be for radiation-force based techniques such as Acoustic Radiation Force Impulse (ARFI) imaging or Shear Wave Elasticity Imaging (SWEI) [8], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to create AKIS images, ventricular motion during atrial contraction is estimated in 3D using Bayesian speckle tracking [17], [18]. Bayesian speckle tracking appropriately weights prior information about the expected motion against a likelihood function scaled based on local data quality.…”
Section: A Motion and Strain Estimationmentioning
confidence: 99%
“…ML and MAP estimations are also performed in the medical US field, for instance, in Refs. [43][44][45], in which a likelihood function is derived for the 1D cross-correlation of local rf-echo data for axial displacement measurement, or a prior is derived for neighboring axial displacements. In this report, a new likelihood function that is derived for the phase difference between a pair of rf-echo signals generated by tissue displacement (vector) and a prior that is derived straightforwardly for the target displacement (vector) are used.…”
Section: Introductionmentioning
confidence: 99%